Adverse childhood experiences, child behavioral health needs, and family characteristics associated with the presence of a firearm in the home: a survey of parents in Chicago - Megan M. Attridge; Marie E. Heffernan; Anne Bendelow; Carly G. Menker; Matthew M. Davis; Karen Sheehan (BMC, 2023)
Abstract Background Firearm violence is the leading cause of pediatric mortality in the USA. The presence of a firearm in the home poses an immense risk to children with increased rates of suicide and unintentional injury by firearm. Recent literature has not explored child ACEs and child behavioral health needs with the presence of a firearm in the home. The objective of this study was to explore an association between these factors, parent health, family experience with firearm violence, and demographics, and the presence of a firearm in the home. Results Overall, 382 of 1,436 (weighted to 22.0%) responding parents reported the presence of a firearm in the home. In an adjusted model, the odds ratio of firearm presence increased incrementally with a child's increasing exposure to ACEs. Compared to a child in the household exposed to no ACEs, a child in the household exposed to two or more ACEs was associated with a 5.16 times higher odds of firearm presence in the home (95% confidence interval (CI) 2.92-9.10). Similarly, a child in the household who had used behavioral health services was associated with a 2.10 times higher odds of firearm presence in the home (95% CI 1.35-3.26), compared to a child in the household who had not. Presence of firearm in the home was also associated with higher household income, younger parent age (under 35 years), and male parent gender. Conclusions Chicago parents have higher odds of reporting the presence of a firearm in the home when living in a household with a child exposed to ACEs and with behavioral health needs. These findings could inform future public health interventions and targeted safe storage messaging to prevent pediatric firearm injury in the home.